Identification and theoretical justification of the core preconditions for the development of digital financial ecosystems - Manoylenko, Oleksandr; Kuznetsova, Svitlana (Технологічний центр, 2026)
The object ofresearch is the process offorming digital fiancial ecosystems in the context of the transformation ofthe global fiancial architecture. The problem is the gaps in the forming digital fiancial ecosystems during the transformation ofthe global fiancial architecture under the inflence oftechnological innovations. This is due to the introduction ofblockchain technologies, smart contracts, intelligent agents (based on the introduction ofartifiial intelligence systems), multi-protocol fiancial technologies, the lack ofunifid standards and regulatory norms. A systems approach, structural-functional, comparative and institutional analysis, as well as trend analysis methods serve as the methodological basis ofthis research, implemented on the basis ofstatistical data from the Statista database and McKinsey & Company reports. Based on the generalization ofquantitative and comparative assessments, the main trends in the transformation ofthe global fiancial architecture have been identifid and analyzed. Institutional changes in the fiancial market based on the introduction ofdecentralized fiancial technologies (DeFi) and the implementation ofthe ISO 20022 regulatory standard are systematized. Key barriers to the transformation of modern fiancial architecture are identifid, and directions for overcoming them are highlighted based on the development ofhybrid fiancial solutions, international unifiation ofstandards and regulatory norms. The concept offorming a hybrid fiancial architecture (CeDeFi) and digital fiancial ecosystems is substantiated, which combines the advantages ofdecentralization and innovation with the reliability ofthe traditional fiancial system. The practical signifiance ofresearch lies in the possibility ofusing its results to form effctive strategies for the development ofdigital fiancial ecosystems, improve regulatory policy and make management decisions by fiancial institutions and fitech companies.
Keywords: digital fiancial ecosystems; fiancial architecture; fiancial technologies; hybrid fiancial architecture